2014
DOI: 10.1038/ajg.2014.242
|View full text |Cite
|
Sign up to set email alerts
|

Four-Year Maintenance Treatment With Adalimumab in Patients with Moderately to Severely Active Ulcerative Colitis: Data from ULTRA 1, 2, and 3

Abstract: OBJECTIVES:The safety and efficacy of adalimumab for patients with moderately to severely active ulcerative colitis (UC) has been reported up to week 52 from the placebo-controlled trials ULTRA (Ulcerative Colitis Long-Term Remission and Maintenance with Adalimumab) 1 and 2. Up to 4 years of data for adalimumab-treated patients from ULTRA 1, 2, and the open-label extension ULTRA 3 are presented.METHODS:Remission per partial Mayo score, remission per Inflammatory Bowel Disease Questionnaire (IBDQ) score, and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
116
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(130 citation statements)
references
References 15 publications
8
116
0
6
Order By: Relevance
“…The basis for these findings may be the presence of several Bio/Tac naïve patients in our study, as these patients showed a high clinical response rate (86.7%) at 12 weeks. In a follow-up study of the UL-TRA 1, 2, and 3 trials, Colombel et al [15] reported that the long-term remission rate at 208 weeks was 24.7%. In our study, the remission rate at both 200 and 350 weeks was 30%, indicating good remission rates beyond 6 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The basis for these findings may be the presence of several Bio/Tac naïve patients in our study, as these patients showed a high clinical response rate (86.7%) at 12 weeks. In a follow-up study of the UL-TRA 1, 2, and 3 trials, Colombel et al [15] reported that the long-term remission rate at 208 weeks was 24.7%. In our study, the remission rate at both 200 and 350 weeks was 30%, indicating good remission rates beyond 6 years.…”
Section: Discussionmentioning
confidence: 99%
“…The ULTRA 2 trial demonstrated efficacy for adalimumab in the maintenance of remission following 52 weeks of treatment. Additionally, in the UL-TRA 3 trial, which included patients who achieved remission at 156 weeks and were evaluated using the partial Mayo score, up to 78.5% of the treated patients maintained remission for 4 years [15]. Recently, results for 4 years of adalimumab maintenance therapy in patients with UC were reported in Japan [16].…”
Section: Introductionmentioning
confidence: 99%
“…Patients were randomly assigned to receive tofacitinib at a dose of 0.5, 3, 10 or 15 mg or placebo twice daily for 8 wk [21] . The primary outcome, clinical response at 8 wk, occurred in 32%, 48%, 61% and 78% of patients receiving tofacitinib at a dose of 0.5 mg (P = 0.39), 3 mg (P = 0.55), 10 mg (P = 0.10), [18] 360 40 mg sc every other week 208 63.6% remission per partial Mayo score at week 208 Golimumab PURSUIT-SC [20] 253 200/100 mg sc 2 wk apart 6 51.6% (P < 0.0001) clinical response at week 6 17.8% (P < 0.0001) clinical remission at week 6 257 400/200 mg sc 2 wk apart 6 54.9% (P < 0.0001) clinical response at week 6 17.9% (P < 0.0001) clinical remission at week 6 PURSUIT-M [7] 151 50 mg sc every 4 wk 54 47% (P = 0.010) clinical response at week 54 23.2% clinical remission at week 54 151 100 mg sc every 4 wk 54 49.7% (P < 0.001) clinical response at week 54 27.8% (P = 0.004) clinical remission at week 54…”
Section: Tofacitinibmentioning
confidence: 99%
“…Up to 4 years of data for adalimumab-treated patients from ULTRA 1 and 2, and the open-label extension ULTRA 3 have been presented [18] . A total of 600/1094 patients enrolled in ULTRA 1 or 2 were randomized to receive adalimumab and induced in the intent to treat analyses.…”
Section: Adalimumabmentioning
confidence: 99%
See 1 more Smart Citation